2016
DOI: 10.1167/iovs.15-18343
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Ultraviolet A Irradiation Leads to Dysfunction of the Limbal Niche Cells and an Antilymphangiogenic and Anti-inflammatory Micromilieu

Abstract: PURPOSE. We analyzed the effects of short-term ultraviolet A (UVA) irradiation on the putative limbal stem cell phenotype, limbal fibroblasts, corneal inflammation, and corneal (lymph)angiogenic privilege.METHODS. Primary human limbal epithelial cells and fibroblasts were irradiated with 5.2 J/cm 2 of UVA. The limbal epithelial cell phenotype was assessed using P63a, cytokeratin 15, integrin b1 (marking stem and transient amplifying cells), and cytokeratin 3 (a differentiation marker) as well as by a colony-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 65 publications
2
11
0
Order By: Relevance
“…The resident epithelial stem cells in the limbus constantly replenish the cornea with epithelial cells which are lost due to normal wear and tear or injury [ 15 ]. Other studies demonstrated that corneal fibroblast signalling permits vessel invasion under pathological conditions [ 78 – 80 ] while our own data illustrated the proangiogenic paracrine activity of human limbal fibroblasts on blood and lymphatic endothelial cells by promoting migration, proliferation, and tube formation compared to human limbal epithelial cells and controls [ 81 ].…”
Section: Angiogenic Privilege and Regulation Of Pro- And Antiangiosupporting
confidence: 52%
See 4 more Smart Citations
“…The resident epithelial stem cells in the limbus constantly replenish the cornea with epithelial cells which are lost due to normal wear and tear or injury [ 15 ]. Other studies demonstrated that corneal fibroblast signalling permits vessel invasion under pathological conditions [ 78 – 80 ] while our own data illustrated the proangiogenic paracrine activity of human limbal fibroblasts on blood and lymphatic endothelial cells by promoting migration, proliferation, and tube formation compared to human limbal epithelial cells and controls [ 81 ].…”
Section: Angiogenic Privilege and Regulation Of Pro- And Antiangiosupporting
confidence: 52%
“…Our group has recently used an in vitro approach to study UVA- and UVB-induced changes in human limbal epithelial cell and fibroblast phenotype and functionality and their paracrine signalling regulating (lymph)angiogenesis and inflammation [ 81 , 122 ].…”
Section: Effects Of Uv Irradiation To the Limbal Niche: Pterygium mentioning
confidence: 99%
See 3 more Smart Citations